2017
DOI: 10.1002/2017jc012756
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shelf‐wide cooling response of a stratified coastal ocean to hurricanes

Abstract: Large uncertainty in the predicted intensity of tropical cyclones (TCs) persists compared to the steadily improving skill in the predicted TC tracks. This intensity uncertainty has its most significant implications in the coastal zone, where TC impacts to populated shorelines are greatest. Recent studies have demonstrated that rapid ahead‐of‐eye‐center cooling of a stratified coastal ocean can have a significant impact on hurricane intensity forecasts. Using observation‐validated, high‐resolution ocean modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…The observed and modeled offshore bottom velocities, stable water column, momentum balance terms, and temperature diagnostics indicate that mixing processes alone were not sufficient for the seaward progression of the Cold Pool Front ∼70 km offshore ahead of Sandy's landfall in New Jersey. The observed ahead‐of‐eye‐center surface cooling was similar to previous studies of tropical cyclones that impacted the MAB during the stratified season such as Irene [ Glenn et al ., ; Seroka et al ., ] and Barry [ Seroka , ]. However, unlike these previous storms Sandy induced an extreme coastal ocean response to a tropical cyclone with the offshore advection of the Cold Pool Front.…”
Section: Discussionmentioning
confidence: 99%
“…The observed and modeled offshore bottom velocities, stable water column, momentum balance terms, and temperature diagnostics indicate that mixing processes alone were not sufficient for the seaward progression of the Cold Pool Front ∼70 km offshore ahead of Sandy's landfall in New Jersey. The observed ahead‐of‐eye‐center surface cooling was similar to previous studies of tropical cyclones that impacted the MAB during the stratified season such as Irene [ Glenn et al ., ; Seroka et al ., ] and Barry [ Seroka , ]. However, unlike these previous storms Sandy induced an extreme coastal ocean response to a tropical cyclone with the offshore advection of the Cold Pool Front.…”
Section: Discussionmentioning
confidence: 99%
“…Longshore winds could generate upwelling or downwelling along the coast. Onshore winds may drive onshore surface currents and offshore bottom currents, and the resulting shear‐induced mixing could lead to rapid ahead‐of‐eye center cooling of the surface mixed layer (Glenn et al, ; Seroka et al, ). Nevertheless, Chen et al () and Chant () reported observations of low‐mode near‐inertial internal waves that are consistent with local wind forcing.…”
Section: Introductionmentioning
confidence: 99%
“…Within the past two decades, extensive research on the deep ocean response to typhoons has taken place (e.g., [1][2][3][4][5][6][7]). In contrast, the impact of a typhoon on coastal waters has been relatively less studied (e.g., [8,9]). Coastal waters yield an important influence on the intensity of a typhoon approaching landfall.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal waters yield an important influence on the intensity of a typhoon approaching landfall. At the same time, a typhoon will also strongly enhance vertical mixing in the near-shore waters, influence volume and heat transport in both along-and cross-shore directions, and alter the marine environment in many ways (e.g., [8,9]). Here, we examine the response examine the response of coastal water in the Taiwan Strait (TWS, Figure 1) following the crossing of Typhoon Nesat in 2017.…”
Section: Introductionmentioning
confidence: 99%